Tuning magnetocaloric effect of Ho1-xGdxNi2 and HoNi2-yCoy alloys around hydrogen liquefaction temperature. (November 2020) - Lai, Jiawei; Tang, Xin; Sepehri-Amin, Hossein; Hono, Kazuhiro
Abstact: We show the giant magnetocaloric effect of HoNi2 compound can be tuned around hydrogen liquefaction temperature by substituting Ho with Gd and Ni with Co in Ho1- x Gd x Ni2- y Co y . While the Curie temperature of Ho1- x Gd x Ni2- y Co y can be tuned from 15 to 32 K originating from the lattice expansion of the cubic structure, giant entropy change of 22.0 J/kgK is retained near the hydrogen liquefaction temperature. A table-like entropy change observed in a broad temperature range of 20 to 32 K makes them promising as magnetocaloric materials for cryogenic magnetic refrigeration utilizing an Ericsson cycle. Graphical abstract: Image, graphical abstract